Literature-based screening and bibliometric analysis of the chemical composition, antioxidant and antimicrobial potential of essential oils isolated from Allium genus: 23 years of investigation - Baby Gargi; Pooja Singh; Sakshi Painuli; Nishant Rai; Prabhakar Semwal; Natália Cruz-Martins; Rohit Sharma (Elsevier, 2024)
Introduction: Various medicinal and aromatic plants possess bioactive components that exhibit therapeutic, cosmetic and pharmaceutical properties. Allium species comprise a subgroup of these medicinal plants which offers these potential advantages. The natural volatile oils derived from these plants have a broad range of functions owing to their richness in bioactive components. Therefore, the interest of presents study is to provide an updated and quantified information regarding the therapeutical commercial products, chemical composition, and biological applications, such as antioxidant and antimicrobial activity of Allium genus essential oils. Methods: This work is designed using a mixed methodology; an extensive data search was conducted for the period from 2000 to 2023 (July). The keywords "Essential oil", "Allium genus", "Bioactive components", "Antimicrobial activity", and "Antioxidant potential", were utilised to extract the data. The information for the literature review was obtained from the PubMed database, while the SCOPUS online database was used for bibliometric analysis. Results: A total of 294 entries were found in PubMed, out of which only 42 studies were selected for comprehensive review based on their experimental approach, including in vivo (1) and in vitro (41) studies. Apart from this, 244 articles were selected and subjected to bibliometric analysis using the VOSviewer and Bibliometrix software. The Allium genus is one of the most representative genera from Amaryllidaceae family, whose therapeutic benefits are properly consolidated in a wide variety of ailments. Traditionally, the Allium species have been consumed in China as spices and vegetables. Although, modern Chinese medicine system have conducted several studies over the years to address the chemical composition, biological applications and commercially available products containing the essential oils of genus Allium. Conclusion: In this sense, this concise review provides an overview of the composition and biological potential (antioxidant and antimicrobial) of the Allium species-derived essential oils. The results from published works also illustrate that these volatile oils are effective in several microbial species and can be exploited as a multi-potent drug against various ailments with advanced safety and efficacy. Although, the integration of past knowledge with current research underscores the enduring significance of Allium essential oils. Furthermore, it highlights the research patterns and future trends in this research domain, providing valuable insights for future researchers to explore this domain further.